2018
DOI: 10.3390/ijms19123964
|View full text |Cite
|
Sign up to set email alerts
|

A Ruthenium(II) N-Heterocyclic Carbene (NHC) Complex with Naphthalimide Ligand Triggers Apoptosis in Colorectal Cancer Cells via Activating the ROS-p38 MAPK Pathway

Abstract: The p38 MAPK pathway is known to influence the anti-tumor effects of several chemotherapeutics, including that of organometallic drugs. Previous studies have demonstrated the important role of p38 both as a regulator and a sensor of cellular reactive oxygen species (ROS) levels. Investigating the anti-cancer properties of novel 1,8-naphthalimide derivatives containing Rh(I) and Ru(II) N-heterocyclic carbene (NHC) ligands, we observed a profound induction of ROS by the complexes, which is most likely generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 40 publications
(74 reference statements)
1
39
0
1
Order By: Relevance
“…The previous research indicates that ruthenium(II) complexes have different effects on the induction of apoptosis in SW480 cells, depending on the ligands in their structure, from a very strong impact where 72% cells were in apoptosis, to moderate, with only 31% apoptotic cells [ 27 ]. In terms of the results related to the ability of ruthenium(II) complexes to induce apoptosis of HCT116 cells, there are results from the previous research that confirm that ruthenium(II) complexes increase the early and late apoptosis of HCT116 in a time- and concentration-dependent manners, but less than oxaliplatin, which is consistent with our results [ 26 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The previous research indicates that ruthenium(II) complexes have different effects on the induction of apoptosis in SW480 cells, depending on the ligands in their structure, from a very strong impact where 72% cells were in apoptosis, to moderate, with only 31% apoptotic cells [ 27 ]. In terms of the results related to the ability of ruthenium(II) complexes to induce apoptosis of HCT116 cells, there are results from the previous research that confirm that ruthenium(II) complexes increase the early and late apoptosis of HCT116 in a time- and concentration-dependent manners, but less than oxaliplatin, which is consistent with our results [ 26 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Many ruthenium(II) complexes can induce apoptosis by different antiproliferative mechanism, whether inducing G0/G1, S or G2/M phase arrest [ 29 , 33 ]. Ru-1 induced the arrest of CT26 and HCT116 cells in the G2/M phase, and Ru-2 caused G2/M phase arrest in SW480 cells, which is likely related to the molecular changes in the cancer cells ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the knowledge of molecular and biochemical mechanisms is of great relevance 3 . The probable mechanisms of action of many recently described ruthenium complexes involve apoptosis 27,32,[36][37][38] .…”
Section: Resultsmentioning
confidence: 99%
“…The MAPK pathway is mainly divided into three components including the p38 MAPK, JNK and ERK pathways, and plays an important role in a variety of events in cell processes (Gary and Johnson, 2002;Xu and Zhang, 2015). Increasing evidence has shown that activated p38 MAPK and SAPK/JNK participated in regulation of p53 and ROSmediated apoptosis (Dabiri et al, 2018;Lan et al, 2017;Shang et al, 2017). Therefore, we determined the effect of PEDV infection on the p38 MAPK and SAPK/JNK signal pathways in Vero cells.…”
Section: Activation Of P53 Is Partly Mediated By Ros Accumulation Upomentioning
confidence: 99%